Partial Glossectomy as an Adjunctive Method to Ortho-Surgical Treatment - Ribeiro, Ney Robson Bezerra; De Freitas Silva, Leonardo [UNESP]; Da Silva, Heitor Fontes; De Carvalho Reis, Erik Neiva Ribeiro [UNESP]; De Oliveira Neto, Jair Queiroz; Maia, Raimundo Nonato; De Jesus Rodrigues Mello, M. (Wolters Kluwer, 2017)
The macroglossia is a rare condition, congenital or acquired, characterized by hypertrophy of the lingual muscles that can cause both aesthetic and functional changes such as mandibular prognathism and malocclusion. Diagnosis is through clinical examination. Treatment consists of excision of part of the tongue and different surgical techniques have been described in the literature. The keyhole lingual resection technique has shown satisfactory results in reducing the volume and preservation of the neurovascular bundles of the tongue. This work aims to present a clinical report of true macroglossia associated with dental-skeletal discrepancies, submitted to partial glossectomy previously to orthognathic surgery.
Keywords: Glossectomy; macroglossia; orthognathic surgery